2009
DOI: 10.1264/jsme2.me09123
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Bacterium Possessing a Haloacid Dehalogenase from a Marine Sediment Core

Abstract: A monobromoacetic acid-resistant bacterium, Bacillus strain I37c, was isolated from a marine sediment core. The strain grew in a medium containing 1.8 mg mL −1 of monobromoacetic acid. It produced constitutively a 2-haloacid dehalogenase that catalyzed the dehalogenation of monobromoacetic acid, monochloroacetic acid, and both L-and D-2-chloropropionic acid. The optimal pH and temperature for the activity measured using a partly purified enzyme were similar to those of known group I haloacid dehalogenases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Most of these microorganisms were isolated from terrestrial environments, with only a few from marine environments, including Burkholderia sp. I37C (Chiba et al, 2009), Rhodobacteraceae sp. (Novak et al, 2013a), Psychromonas such as barophilicity, salt tolerance, cold adaptability, hyperthermostability, chemoselectivity, stereoselectivity, and regioselectivity (Thippeswamy et al, 2021;Zhang J. et al, 2021).…”
Section: Isolation Sources and Classification Of 2-haloacid Dehalogenasesmentioning
confidence: 99%
“…Most of these microorganisms were isolated from terrestrial environments, with only a few from marine environments, including Burkholderia sp. I37C (Chiba et al, 2009), Rhodobacteraceae sp. (Novak et al, 2013a), Psychromonas such as barophilicity, salt tolerance, cold adaptability, hyperthermostability, chemoselectivity, stereoselectivity, and regioselectivity (Thippeswamy et al, 2021;Zhang J. et al, 2021).…”
Section: Isolation Sources and Classification Of 2-haloacid Dehalogenasesmentioning
confidence: 99%
“…Over the past decade, a variety of thermophilic (Rye et al 2009), psychrophilic (Drienovska et al 2012;Novak et al 2013), and non-extremophilic microbes capable of degrading 2,4-D (Fulthorpe et al 1995;González et al 2012;Kumar et al 2014;Samir et al 2015) have been isolated from contaminated marine environments (Chiba et al 2009;Fulthorpe et al 1995;González et al 2012;Kumar et al 2014;Novak et al 2014;Samir et al 2015). However, studies on bioremediation of chlorinated compounds under hypersaline environments are sparse.…”
Section: Degradation Of Halogenated Hydrocarbons By Halophilic Bactermentioning
confidence: 99%
“…Yoshida et al (174) reported that an enrichment culture containing Dehalobacter species was able to reductively dechlorinate PCDDs and PCBs. In addition, Chiba et al (16) reported that a Bacillus strain isolated from a marine sediment core had a haloacid dehalogenase that catalyzed the dehalogenation of monobromoacetic acid, monochloroacetic acid, and 2-chloropropionic acid.…”
Section: Biodegradation Of Hazardous Chemicals: One Of the Fastest Grmentioning
confidence: 99%